2018
DOI: 10.1002/jts.22271
|View full text |Cite
|
Sign up to set email alerts
|

Narratives in the Immediate Aftermath of Traumatic Injury: Markers of Ongoing Depressive and Posttraumatic Stress Disorder Symptoms

Abstract: In this study, we considered connections between the content of immediate trauma narratives and longitudinal trajectories of negative symptoms to address questions about the timing and predictive value of collected trauma narratives. Participants (N = 68) were individuals who were admitted to the emergency department of a metropolitan hospital and provided narrative recollections of the traumatic event that brought them into the hospital that day. They were then assessed at intervals over the next 12 months fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 46 publications
(65 reference statements)
0
14
1
Order By: Relevance
“…In fact, the approach to access mental states by analyzing patterns of language usage is supported by a growing body of research in the fields of psychology and neuroscience . Previous studies using Linguistic Inquiry and Word Count (LIWC) have found that it is possible to characterize depression and other mental states through analyzing natural language use (Tausczik and Pennebaker, 2010;Booker et al, 2018;Kaplow et al, 2018;Tackman et al, 2018). For example, Stirman and Pennebaker showed that suicidal poets displayed a higher usage of first person pronouns in their texts and less first-plural pronouns than non-suicidal poets (Stirman and Pennebaker, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the approach to access mental states by analyzing patterns of language usage is supported by a growing body of research in the fields of psychology and neuroscience . Previous studies using Linguistic Inquiry and Word Count (LIWC) have found that it is possible to characterize depression and other mental states through analyzing natural language use (Tausczik and Pennebaker, 2010;Booker et al, 2018;Kaplow et al, 2018;Tackman et al, 2018). For example, Stirman and Pennebaker showed that suicidal poets displayed a higher usage of first person pronouns in their texts and less first-plural pronouns than non-suicidal poets (Stirman and Pennebaker, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The current study sought to examine clinical associations of language use in nightmare transcriptions and rescriptions to psychological functioning. This study extends the current literature about language use and posttrauma psychological functioning (e.g., Booker et al, 2018; Kleim et al, 2018) with a specific focus on the novel use of LIWC with PTNMs. The present study had several hypotheses regarding the relationship of language use to psychological symptoms by focusing specifically on words related to cognitive processing and ET, as these constructs have been previously implicated in psychological functioning.…”
Section: Discussionmentioning
confidence: 61%
“…The content of PTNMs is also associated with nightmare severity and PTSD symptom severity, such that as the content of PTNMs becomes more similar to the trauma, the more severe the nightmares and symptoms of PTSD are reported (Davis et al, 2007; Mellman et al, 1995). There is limited research on language use in PTNM narratives; however, researchers have investigated language use in idiopathic nightmares and trauma narratives (i.e., Booker et al, 2018; Bulkeley & Graves, 2018; Fireman et al, 2014; Kleim et al, 2018). As rescription involves the process of rewriting the original PTNM to include alternative responses or outcomes to the event, it will be important to study the language use in rescripted PTNMs as well, which has yet to be done.…”
mentioning
confidence: 99%
“…It is known that a high frequency of singular and plural first pronoun usage is an indicator of depression and PTSD 25,[73][74][75][76][77][78] . We examined singular first pronoun occurrence in text data from Holocaust survivors, controls and PTSD sufferers, consisting of people who experienced trauma years ago, including childhood trauma.…”
Section: Resultsmentioning
confidence: 99%